2006
DOI: 10.1101/gad.388206
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd2b antagonizes H3K9 trimethylation at pericentric heterochromatin in mammalian cells

Abstract: Histone lysine trimethyl states represent some of the most robust epigenetic modifications in eukaryotic chromatin. Using a candidate approach, we identified the subgroup of murine Jmjd2 proteins to antagonize H3K9me3 at pericentric heterochromatin. H3K27me3 and H4K20me3 marks are not impaired in inducible Jmjd2b-GFP cell lines, but Jmjd2b also reduces H3K36 methylation. Since recombinant Jmjd2b appears as a very poor enzyme, we applied metabolic labeling with heavy methyl groups to demonstrate Jmjd2b-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
304
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(320 citation statements)
references
References 37 publications
16
304
0
Order By: Relevance
“…As stated before, JMJD2B has been demonstrated to be able to demethylate H3K9me3 at pericentric heterochromatin in mammalian cells (20,21). In light of our observation that JMJD2B influences ERα-regulated transcription and its demethylase activity is essential for that effect, it is logical to postulate that JMJD2B may also function in euchromatin regions and act to erase the H3K9me3 mark in ERα-activated transcription.…”
Section: Jmjd2b/mll2 Complex Is Associated With Erα and Is Required Formentioning
confidence: 82%
See 2 more Smart Citations
“…As stated before, JMJD2B has been demonstrated to be able to demethylate H3K9me3 at pericentric heterochromatin in mammalian cells (20,21). In light of our observation that JMJD2B influences ERα-regulated transcription and its demethylase activity is essential for that effect, it is logical to postulate that JMJD2B may also function in euchromatin regions and act to erase the H3K9me3 mark in ERα-activated transcription.…”
Section: Jmjd2b/mll2 Complex Is Associated With Erα and Is Required Formentioning
confidence: 82%
“…To further support this observation and to investigate whether or not H3K4 methylation is affected by H3K9me3 demethylation, mouse Jmjd2b (W-mJmjd2b or M-mJmjd2b) (20,28) was transfected into JMJD2B-depleted (with stable transfection of JMJD2B-specific siRNA molecules) MCF-7 cells. These cells were deprived of estrogen for 3 d and then treated with E2.…”
Section: Functional Coordination Between the Mll2 Complex And Jmjd2bmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ectopic expression of JMJD2A, -B and -C significantly decreased H3K9me3/2 levels, and delocalized HP1. 14,38 Thus, cancer cells with high expression of JMJD2 might evade this important tumor suppressor mechanism. 14 In agreement with the oncogenic potential of JMJD2 to tumor development, overexpression of JMJD2 proteins was observed in prostate cancer.…”
Section: Gasc1/jmjd2c/kdm4cmentioning
confidence: 99%
“…Though histone methylation was originally considered irreversible, recent studies have demonstrated that it can be reversed by several histone demethylases including PAD4/ PADI4, BHC110/LSD1 and a new family of JmjC domain-containing histone demethylases (Cloos et al, 2006;Cuthbert et al, 2004;Fodor et al, 2006;Klose et al, 2006;Shi et al, 2004;Tsukada et al, 2006;Wang et al, 2004;Whetstine et al, 2006;Yamane et al, 2006).…”
Section: Introductionmentioning
confidence: 99%